UCH-L1 and GFAP Serum Levels in Neonates with Hypoxic–Ischemic Encephalopathy: A Single Center Pilot Study - Douglas-Escobar, Martha V.; Heaton, Shelley C.; Bennett, Jeffrey; Young, Linda J.; Glushakova, Olena; Xu, Xiaohui; Barbeau, Daphna Yasova; Rossignol, Candice; Miller, Cindy; Old Crow, Alissa M.; Hayes, Ronald L.; Weiss, Michael D. (Frontiers in Neurology, 2014)
Objective: We examined two potential biomarkers of brain damage in hypoxic–ischemic encephalopathy (HIE) neonates: glial fibrillary acidic protein (GFAP; a marker of gliosis) and ubiquitin C-terminal hydrolase L1 (UCH-L1; a marker of neuronal injury). We hypothesized that the biomarkers would be measurable in cord blood of healthy neonates and could serve as a normative reference for brain injury in HIE infants. We further hypothesized that higher levels would be detected in serum samples of HIE neonates and would correlate with brain damage on magnetic resonance imaging (MRI) and later developmental outcomes.? Study Design: Serum UCH-L1 and GFAP concentrations from HIE neonates (n = 16) were compared to controls (n = 11). The relationship between biomarker concentrations of HIE neonates and brain damage (MRI) and developmental outcomes (Bayley-III) was examined using Pearson correlation coefficients and a mixed model design. Result: Both biomarkers were detectable in cord blood from control subjects. UCH-L1 concentrations were higher in HIE neonates (p < 0.001), and associated with cortical injury (p < 0.055) and later motor and cognitive developmental outcomes (p < 0.05). The temporal change in GFAP concentrations during (from birth to 96 h of age) predicted motor developmental outcomes (p < 0.05) and injury to the basal ganglia and white matter. Conclusion: Ubiquitin C-terminal hydrolase L1 and GFAP should be explored further as promising serum biomarkers of brain damage and later neurodevelopmental outcomes in neonates with HIE.